Analisis Kontekstual Adegan Pernikahan Ratu Ayu Kencanawungu Dalam Tari Langendriyan - Sutarno Haryono (Greget, 2013)
The overall appearance of a dance is not a construction of which the elements can be analyzed individually but rather a complete and rounded unit (gestalt). Therefore, presentational symbols rather than discursive symbols emerge. Presentational symbols point to the hidden meaning behind the meaning that is directly visible, or reveal a level of meaning that is presupposed within the literal meaning. Of course, when interpreting the meaning of an art which contains a number of different elements, such as dance, a highly complex unit is observed which is made up of all the different elements that cannot be separated one from another. Keywords : Analysis, Contextual, Macapat, and Dance Movements.